Public service sector decisions: A literature study on the role of government and community collaboration in decision-making processes - Dharmawan, Eka Wira; Warsono, Hardi; Kismartini, Kismartini; Astuti, Retno Sunu (Edelweiss Applied Science and Technology, 2025)
The importance of government and community collaboration during the decision-making process in the public service sector using collaboration methods is significant. The application of this collaboration is considered an effective strategy to improve public services as desired by the community. For this reason, the government needs to collaborate with the community in making public service policy decisions. By using the literature study method, this research found that collaboration is a form of innovation that fosters a shared understanding between the parties involved. This common understanding can take the form of a vision, mission, and goals. Although there are still many challenges that need to be faced, most of these government and community collaboration projects have yielded positive results and improved public services more effectively.